2018
DOI: 10.1186/s40478-017-0506-9
|View full text |Cite
|
Sign up to set email alerts
|

Surfen, a proteoglycan binding agent, reduces inflammation but inhibits remyelination in murine models of Multiple Sclerosis

Abstract: Proteoglycans are promising therapeutic targets in Multiple Sclerosis (MS), because they regulate many aspects of the immune response. This was studied using surfen, an agent that binds both heparan sulphate proteoglycans (HSPGs) and chondroitin sulphate proteoglycans (CSPGs). Initial cell culture work on bone marrow derived macrophages (BMDMs) found that surfen reduced concentrations of the chemokines CCL2, CCL4 and CCL5, with reduced messenger (m)RNA expression for Tumor Necrosis Factor, IL-6, IL-1β and indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Consistent with this finding, decreased SRGN expression has been reported in olfactory epithelium biopsy samples from subjects with SZ in association with visual learning and memory performance (Horiuchi et al., 2016). The expression of SRGN in the brain has not been well characterized, although it has been reported to increase in experimental autoimmune encephalomyelitis in mice and in glioma (Roy et al., 2017; Warford et al., 2018). In human amygdala, we found that SRGN protein product is observed as a distinctly punctate labelling within the neuron cytoplasm (Figure 8), suggesting a vesicular localization potentially consistent with SRGN expression in mast cells and hematopoietic cells, where it is located in cytoplasmic secretory granules, and binds to several cytokines and growth factors (Korpetinou et al., 2014; Sarrazin et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, decreased SRGN expression has been reported in olfactory epithelium biopsy samples from subjects with SZ in association with visual learning and memory performance (Horiuchi et al., 2016). The expression of SRGN in the brain has not been well characterized, although it has been reported to increase in experimental autoimmune encephalomyelitis in mice and in glioma (Roy et al., 2017; Warford et al., 2018). In human amygdala, we found that SRGN protein product is observed as a distinctly punctate labelling within the neuron cytoplasm (Figure 8), suggesting a vesicular localization potentially consistent with SRGN expression in mast cells and hematopoietic cells, where it is located in cytoplasmic secretory granules, and binds to several cytokines and growth factors (Korpetinou et al., 2014; Sarrazin et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Because of their cellular location, focal adhesions play a role in signal transduction and have been suggested to function as mechanosensors in mature endothelial cells [ 54 ]. Surfen inhibits the interaction of proteoglycans with the focal adhesion complexes [ 55 ] and thereby truncated HIF-1α stabilisation due to mechanical strain in PDLF. These data strongly indicate an association between the interaction of proteoglycans with focal adhesion sites and mechanotransductive stabilisation of HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some CSPGs (such as versican) are well known to inhibit remyelination, but others (such as aggrecan) may also be essential as protective factors during inflammation. In this respect, surfen, a compound known to bind the GAG side chains of proteoglycans with high affinity, has shown a protective effect in the EAE model, but a detrimental effect in the LPC model [100], probably due to a generalized increase in CSPG expression.…”
Section: Chondroitin Sulfate Proteoglycansmentioning
confidence: 99%